NILAI-NILAI PENDIDIKAN DALAM KOMIK “NARUTO” DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM (Kajian Materi) - SAPUTRA, ANDI (Universitas Islam Negeri Raden Intan Lampung, 2014)
This article aims at discovering and analyzing educational values in the Naruto comic critically and finding its relevance to Islamic education by focusing on the material aspects of the comic series, volume 1 – 30. True education is the gateway to usher humanity toward a higher civilization and humanist with alignment based on the human relationships, the environment, and the creator. To achieve the goal of education, in this case, a learning material plays a very crucial role. It is because the material is an operational part of education. Various parties related to the education, especially teachers, are always required to master and understand the materials to be delivered to the learners. Considering learning materials occupies a very important position of the whole curriculum which should be prepared in order to achieve the implementation of learning objectives, in this case, Naruto can be used as a teaching material, in which its story conveys propositions or ideas. Besides, Naruto has tremendous appeal, so that the message is easily digested and understood, and it does not seem also to be patronizing. Although the material which is in the form of the story presented in Naruto is very limited, but from the aspect of material absorption, the messages in the comic story is much lighter to digest